Steroid diversification by multicomponent reactions - Reguera, Leslie (2019)
Reports on structural diversification of steroids by means of multicomponent reactions (MCRs) have significantly increased over the last decade. This review covers the most relevant strategies dealing with the use of steroidal substrates in MCRs, including the synthesis of steroidal heterocycles and macrocycles as well as the conjugation of steroids to amino acids, peptides and carbohydrates. We demonstrate that steroids are available with almost all types of MCR reactive functionalities, e.g., carbonyl, carboxylic acid, alkyne, amine, isocyanide, boronic acid, etc., and that steroids are suitable starting materials for relevant MCRs such as those based on imine and isocyanide. The focus is mainly posed on proving the amenability of MCRs for the diversityoriented derivatization of naturally occurring steroids and the construction of complex steroid-based platforms for drug discovery, chemical biology and supramolecular chemistry applications.